Cover Feature: Isolation and Characterization of Different Homometallic and Heterobimetallic Complexes of Nickel and Zinc Ions by Controlling Molar Ratios and Solvents (Eur. J. Inorg. Chem. 24/2019). Issue 24 (12th June 2019) - Kushvaha, Saroj Kumar; Arumugam, Selvakumar; Shankar, Bhaskaran; Sarkar, Rabi Shankar; Ramkumar, Venkatachalam; Mondal, Kartik Chandra
Abstract : The Cover Feature shows the isolation of homometallic and heterobimetallic clusters of nickel and zinc ions by controlling the solvents and the molar ratios of the substrates. The picture also highlights the fluorescence properties of zinc clusters and the magnetic properties of mixed metallic clusters of nickel and zinc ions. More information can be found in the Full Paper by K. C. Mondal et al.